2016
DOI: 10.1097/md.0000000000004864
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of congenital dysfibrinogenemia in unrelated Chinese families

Abstract: Congenital dysfibrinogenemia (CD) is a qualitative fibrinogen disorder caused by an abnormal fibrinogen molecule structure, leading to dysfunctional blood coagulation. This study describes 3 cases of dysfibrinogenemia identified in the unrelated Chinese pedigrees.Routine coagulation screening tests were performed on the probands and their families. The antigens and functionality of fibrinogen was measured using an immunoturbidimetry assay and the Clauss method, respectively. To identify the genetic mutation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 32 publications
5
96
0
Order By: Relevance
“…28 Various studies conducted in different Asian countries, ie China, Hong Kong, Saudi Arabia, UAE and Iran, using MMAS-8 have also reported similar poor adherence to prescribed antihypertensive therapy, supporting our results. 15,[29][30][31][32][33][34][35] The WHO estimates the prevalence of non-adherence among patients with chronic diseases to be between 52% and 74%, defined by ≥80% cut-off. 36 In this study, we found no significant correlation between gender and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Various studies conducted in different Asian countries, ie China, Hong Kong, Saudi Arabia, UAE and Iran, using MMAS-8 have also reported similar poor adherence to prescribed antihypertensive therapy, supporting our results. 15,[29][30][31][32][33][34][35] The WHO estimates the prevalence of non-adherence among patients with chronic diseases to be between 52% and 74%, defined by ≥80% cut-off. 36 In this study, we found no significant correlation between gender and medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal adherence to prescribed antihypertensive therapy may result in substantial reductions in the incidence of myocardial infarction (20-25%), heart failure (>50%) and stroke (35-40%). 15,16 Various barriers to antihypertensive medication adherence have been previously identified and reported in the literature. These include cost of medication, lack of education, forgetfulness, unavailability, too much medication, fear of addiction and possible side effects, and dissatisfaction with the therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing the immune cell repertoire in healthy adults found that PD-1 expression is higher in Vδ1+, compared to Vδ2 + T-cells 15 but similar within several functionally distinctive subsets of Vδ2 T-cells. 16 Others reported differences in PD-1 expression depending on CD27 and CD45RA status with preferential expression in the effector-memory subsets.…”
Section: Expression Of Pd-1 By γδ T-cells In Health and Diseasementioning
confidence: 99%
“…7 Patients with common variable immunodeficiency (CVID) have less Vδ2 T-cells but the remaining cells express more PD-1. 15 In cancer, higher expression of PD-1 was described in γδ T-cells isolated from neuroblastoma 14 and colorectal cancer tissues 17 as well as multiple myeloma (MM) infiltrated BM. 6 Daley et al examined immune cell infiltration of pancreatic ductal adenocarcinoma tissues in humans and found that γδ T-cells were highly enriched compared to normal pancreas.…”
Section: Expression Of Pd-1 By γδ T-cells In Health and Diseasementioning
confidence: 99%
“…16,21 Bile acid (BA) metabolism was reported to be involved in cholesterol as well as glucose metabolism homeostasis. 29 The latter authors claimed that insulin resistance is positively associated with hyperbileacidemia regardless of diabetes status, which indicates the important role of insulin resistance in the regulation of "bile secretion" pathway in human. BAs also exert a variety of metabolic reactions as they likely promote the secretion of incretin in the digestive tract, improve glucose tolerance, promote insulin secretion, thus positively increase insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%